Narrative Review: Human Capital, Technology Capital, Digital Capabilities in Organizational Performance SMEs in the Era of Digitalization - Choirul Anam; Sopiah Sopiah (Department of Management, Faculty of Economics and Business, Brawijaya University, 2024)
Small and medium-sized enterprises (SMEs) in the age of digitalization need new strategies to optimize their organizational performance. Human Capital, Technology Capital, and Digital Capabilities are critical factors in achieving optimal performance in an increasingly digitalized business environment. This study identifies the role of each factor in achieving optimal performance in SMEs and shows the importance of developing digital capabilities in the digitalization era. In addition, this study also highlights the importance of interactions between these factors and their influence on organizational performance. The Systematic Literature Review approach is the researcher's footing to review more in-depth previous research regarding human capital, technology capital, and digital capabilities in the scope of SME organizational performance with the Narrative Review method. The data collected were 207 articles from the Scopus and Google Scholar databases. Then, it was eliminated to 30 articles according to the SPIDER criteria. This study shows that improving human capital, technology capital, and digital capabilities can help SMEs maintain their position in the digitalization era and improve their performance